Epstein-Barr Virus Latent Membrane Protein-1 Effects on Plakoglobin, Cell Growth and Migration - Shair, Kathy H.Y (2008)
Latent membrane protein-1 (LMP1), the major oncoprotein of Epstein-Barr virus (EBV), is likely responsible for many of the altered cellular growth properties in EBV-associated cancers including nasopharyngeal carcinoma (NPC). In this study, the effects of LMP1 on cell growth and migration were studied in the context of the EBV-positive C666-1 NPC cell line. In the soft agar transformation and transwell metastasis assays, LMP1 enhanced cell growth and migration through activation of phosphatidylinositol 3-kinase (PI3K)/Akt and NFκB signaling. Inhibitors of PI3K, Akt and NFκB signaling dramatically reduced these enhanced properties. An IκBα super-repressor also blocked these effects. However, constitutive activation of Akt alone did not alter cell growth, suggesting that both PI3K/Akt and NFκB activation are required by LMP1. These enhanced effects required the full-length LMP1 encompassing both the PI3K/Akt activating C-terminal activation region (CTAR) 1 and the non-redundant NFκB activating regions CTARs 1 and 2. LMP2A, a latent protein that is also frequently expressed in NPC, similarly activates the PI3K/Akt pathway, however its over-expression in C666-1 cells did not affect cell growth or migration. LMP1 also decreased expression of the junctional protein plakoglobin which was shown to be partially responsible for enhanced migration induced by LMP1. This study reveals that in epithelial cells the transforming properties of LMP1 require activation of both PI3K/Akt and NFκB and demonstrates that the loss of plakoglobin expression by LMP1 is a significant factor in the enhanced migration.